Studying the Behavior of Expansive Soil Reinforced by Micropiles - Ahmed S. A. Al-Gharbawi; Ahmed M. Najemalden; Mohammed Y. Fattah (Salehan Institute of Higher Education, 2024)
Expansive soil is a form of soil that can expand and contract, changing its volume. Montmorillonite, a mineral with the ability to dissolve in water, makes up the majority of these kinds of soils, and by increasing the volume of the soil, it causes the soil to heave. Expansive soils could be a substantial concern for engineered buildings due to their capacity to adjust to seasonal variations by contracting or expanding moisture content. Many researchers focused on soils that were swollen and looked at how they behaved as well as how they could be improved. In this study, the work depends on inserting micro-piles with different depths and configuration widths to investigate which depth and configuration can be obtained to improve the bearing capacity of foundations on expansive soil. The main purpose of this study is to reinforce the expansive soil with micro-piles with different depths (1B, 2B, and 3B) and different configuration widths (under footing only, 1B and 2B). It was concluded that the soil reinforced with micro-piles improved the load-bearing capacity of the expensive soil and decreased the swell pressure. The increasing depth of the micropiles 2B to 3B (B is the width/diameter of the foundation) can increase the bearing capacity by just 6%; therefore, increasing the depth beyond 2B is not beneficial. Also, the increase in width of the configuration of the micro piles from 1B to 2B increases the bearing capacity by just 4%; therefore, the increase in width greater than 1B is not valid. Doi: 10.28991/CEJ-2024-010-01-017 Full Text: PDF